Insight-HXMT observations of jet-like corona in a black hole X-ray binary MAXI J1820+070 - Bei You (Nature Portfolio, 2021)
Evolution of accretion disk and corona during outbursts in black hole binary systems is still unclear. Here, the authors show spectral analysis of MAXI J1820+070 and propose a scenario of a dynamical corona to explain the evolution of the reflection fraction observed by Insight-HXMT.